THE ROLE OF ZAKAT FOR POVERTY ALLEVIATION IN INDONESIA : BIBLIOGRAPHIC STUDY - Zainal Alim Adiwijaya; Rita Rosalina (LPPM STIE Muhammadiah Bandung, 2026)
Poverty is one of the main problems that occurs in developing countries, including Indonesia. This research tries to describe poverty alleviation in developing countries through the role of zakat from Scopus-indexed journals and accredited journals in Indonesia that represent rural areas in Indonesia. Samples were obtained from 10 articles discussing zakat for poverty alleviation. The author classifies these articles based on research topics, methods, and models. The topic of zakat antecedents is a topic that has been widely studied. The analytical method and modified Jones accrual model are the most popular models used because this model is considered the most appropriate for measuring the role of zakat in poverty alleviation compared to other models. Through zakat, it is expected that the economy will develop further, and the problem of poverty can gradually be resolved